CARL ALLEN'S STRUGGLE FOR SUPERIORITY IN YES MAN MOVIEBY PEYTON REED (2008): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KUSUMANINGRUM, DYAH (2010)
The object of the research is the movie entitled Yes Man directed by Peyton Reed. The objective of the study is to examine how struggle for superiority of the major character is reflected in Carl Allen's Yes Man based on individual psychological approach and the structural elements. The research is conducted by using qualitative method; the writer uses two data sources, namely primary and secondary data source. The primary data is movie Yes Man directed by Peyton Reed. The secondary data sources are the other sources related to the analysis like theory of mise-en-scene and design. The method of the data collection is observation. The technique of data analysis is descriptive analysis. The results of the research are as follows. Firstly, the structural element of the movie presents a solid unity. Secondly, the individual psychological analysis shows that the struggle for superiority of Carl Allen comes from his fictional finalism and is supported by his inferiority feeling. It makes him strive to reach the superiority and power in emerging the struggle for life by joining "Yes" seminar. In the end, it can be concluded that the struggle for freedom can find happiness. Finally, Carl Allen gets his struggle for superiority after he says yes for every good opportunity, he takes some courses, he helps everyone and becomes nice person and everybody loves him.